Closure of ‘Third Places’? Exploring Potential Consequences for Collective Health and Wellbeing - Finlay, Jessica (Health Place, 2019)
In unassuming neighborhood locales, such as coffee shops, hair salons, and malls, people meet to socialize, express themselves, and support one another. These ‘third places’ enrich social interaction, sense of community, and belonging outside of the home and workplace. Yet third places are closing across the United States. Americans may be losing access to key services, goods, and amenities, in addition to community sites that help buffer against loneliness, stress, and alienation. The relevance of third places to health and quality life is under-researched. These sites may support wellbeing through mechanisms of stimulation, support, protection, and care. We call on researchers to investigate how third places contribute to wellbeing and consider the consequences that the disappearance of such places has for public health. Future research on third places may be mobilized to innovatively reduce health disparities and improve quality of life.